2009
DOI: 10.1097/ta.0b013e3181bbf728
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Shock Index in Predicting Mortality in Traumatically Injured Patients

Abstract: Trauma patients with SI >0.9 have higher mortality rates. An increase in SI from the field to the ED may predict higher mortality. The SI may be a valuable addition to other ED triage criteria currently used to activate trauma team responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
226
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(258 citation statements)
references
References 16 publications
6
226
2
5
Order By: Relevance
“…However, regarding the relationship between age and sex in patients with a recorded shock index score, King et al (11) agree and Cannon et al (12) disagree with the findings of this study. In this study, penetrating trauma was significantly related to shock index, which has been previously confirmed (4,13).…”
Section: Discussioncontrasting
confidence: 53%
“…However, regarding the relationship between age and sex in patients with a recorded shock index score, King et al (11) agree and Cannon et al (12) disagree with the findings of this study. In this study, penetrating trauma was significantly related to shock index, which has been previously confirmed (4,13).…”
Section: Discussioncontrasting
confidence: 53%
“…This was comparable to Yavuz Simsek et al [5] who found it to be 84.7 %, Patil et al [6] 93 %, Naithani et al [7] 95.83 % and Domingo et al [8] 81 % . The mean shock index (heart rate/systolic blood pressure) of the women in our study was very high (0.94 ± 0.26), while normal SI was 0.5-0.7 [9,10]. The higher the shock index, the greater the severity of shock.…”
Section: Discussionmentioning
confidence: 48%
“…The prognostic significance of the shock index was investigated in different populations of critically ill patients in the setting of trauma, surgery or sepsis. 6, 7 Nevertheless, there are only sparse data addressing the prognostic value of the shock index in patients with STEMI. 8- 10 Furthermore, the relationship of the shock index with myocardial damage has not been previously examined.…”
mentioning
confidence: 99%